2022
DOI: 10.1101/2022.06.02.494376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancer architecture and chromatin accessibility constrain phenotypic space during development

Abstract: Developmental enhancers are DNA sequences that when bound to transcription factors dictate specific patterns of gene expression during development. It has been proposed that the evolution of such cis-regulatory elements is a major source of adaptive evolution; however, the regulatory and evolutionary potential of such elements remains little understood, masked by selective constraints, drift and contingency. Here, using mutation libraries inDrosophila melanogasterembryos, we observed that most mutations in cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Nonetheless, testing random sequences within the context of developing embryos could provide another source of data to understand how enhancers encode tissue-specific expression. 90 In the future, integration of genomic regions, synthetic designed, and random sequences will contribute to our understanding of enhancer grammar. Despite the complexity of studying enhancers in developing embryos, our study demonstrates that enhancer grammar is critical for encoding notochord activity and our observation of the same logics and grammar signatures in both Ciona and vertebrates hints at conservation of these grammatical constraints across chordates.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, testing random sequences within the context of developing embryos could provide another source of data to understand how enhancers encode tissue-specific expression. 90 In the future, integration of genomic regions, synthetic designed, and random sequences will contribute to our understanding of enhancer grammar. Despite the complexity of studying enhancers in developing embryos, our study demonstrates that enhancer grammar is critical for encoding notochord activity and our observation of the same logics and grammar signatures in both Ciona and vertebrates hints at conservation of these grammatical constraints across chordates.…”
Section: Discussionmentioning
confidence: 99%
“…Testing random sequences has proven to be an effective strategy for isolating functional nucleic acids 104 and proteins 105 , learning 5'UTR 106,107 , splicing 108,109 , and polyadenylation logic 110 . Importantly, random sequences have developmental enhancer activity 111 , and we recently showed that random DNA provides ideal data for deciphering cis-regulation 14,25,31 . For instance, our (de Boer) recent proof-of-principle study in yeast showed that random DNA had diverse cis-regulatory activity, and this enabled us to design an experiment for simultaneous quantification of the expression levels encoded by each of >30 million random 80 bp sequences (~2.4Gb of regulatory DNA; 184 yeast genome equivalents) 25 .…”
Section: Synthetic Dna As a Potential Solutionmentioning
confidence: 99%
“…While learning cis-regulation from measurements of random DNA activity may seem counter-intuitive, the reason why this works is simple: there are many TFs (~1,639 in humans 2 ), and their binding sites occur frequently by chance 25,111,112 , enabling one to select for binding sites for individual TFs or pairs of TFs from random DNA 37,113,114 . While a random sequence having a binding site for a specific TF is unlikely, it is almost certain to have binding sites for some TF, leading to high expression diversity among random sequences 25 , and distinct expression programs across cell types 111,115 . This propensity for random sequences to frequently be active is also consistent with the soft regulatory syntax of the billboard model 23 .…”
Section: Synthetic Dna As a Potential Solutionmentioning
confidence: 99%
“…Drosophila embryos were fixed and stained following standard protocols 73 . In particular, stage-5 embryos were acquired from a 5-hr egg-laying window at room temperature.…”
Section: Embryo Fixation Antibody Staining and Fluorescent In Situ Hy...mentioning
confidence: 99%